PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT UPAYA MENINGKATKAN PEMAHAMAN BELAJAR - Maydiantoro, Albet (Metafora: Education, Social Sciences and Humanities Journal, 2015)
This research was aimed at analyzing the use of cooperative learning model of Teams Tournament Games to improve the eleventh grade students’ understanding of social science at Bina Latih Karya Vocational High School Bandar Lampung. It was conducted through classroom action research approach. Classroom action research is a kind of research conducted by education practitioners in collaboration with colleagues to improve the quality of classroom learning processes and outcomes without disrupting the learning process. The results showed that students’ understanding of Social Science increased significantly. It could be viewed from the results of students’ learning; the pre-action score was 44.22 on average, in Cycle 1 the score increased by an average of 74.51; in cycle 2 it became 75.44; and in Cycle 3 students’ average score increased by an average of 79.96. The TGT type of cooperative learning in the learning process could improve the understanding of students’ learning.